The Entner-Doudoroff Pathway Contributes to Glycogen Breakdown During High to Low CO2 Shifts in the Cyanobacterium Synechocystis sp. PCC 6803 - Lucius, Stefan; Makowka, Alexander; Michl, Klaudia; Gutekunst, Kirstin; Hagemann, Martin (Frontiers in Plant Science, 2021)
Cyanobacteria perform plant-like oxygenic photosynthesis to convert inorganic carbon in organic compounds and can also use internal carbohydrate reserves under specific conditions. A mutant collection with defects in different routes for sugar catabolism was studied to analyze which of them is preferentially used to degrade glycogen reserves in light-exposed cells of Synechocystis sp. PCC 6803 shifted from high to low CO2 conditions. Mutants defective in the glycolytic Embden–Meyerhof–Parnas pathway or in the oxidative pentose-phosphate (OPP) pathway showed glycogen levels similar to wild type under high CO2 (HC) conditions and were able to degrade it similarly after shifts to low CO2 (LC) conditions. In contrast, the mutant eda, which is defective in the glycolytic Entner-Doudoroff (ED) pathway, accumulated elevated glycogen levels under HC that were more slowly consumed during the LC shift. In consequence, the mutant eda showed a lowered ability to respond to the inorganic carbon shifts, displayed a pronounced lack in the reactivation of growth when brought back to HC, and differed significantly in its metabolite composition. Particularly, eda accumulated enhanced levels of proline, which is a well-known metabolite to maintain redox balances via NADPH levels in many organisms under stress conditions. We suggest that deletion of eda might promote the utilization of the OPP shunt that dramatically enhance NADPH levels. Collectively, the results point at a major regulatory contribution of the ED pathway for the mobilization of glycogen reserves during rapid acclimation to fluctuating CO2 conditions.